Termination of Vernakalant-Resistant Atrial Fibrillation by Inhibition of Small-Conductance Ca2+-Activated K+ Channels in Pigs. (October 2017) - Diness, Jonas Goldin; Skibsbye, Lasse; Simó-Vicens, Rafel; Santos, Joana Larupa; Lundegaard, Pia; Citerni, Carlotta; Sauter, Daniel Rafael Peter; Bomholtz, Sofia Hammami; Svendsen, Jesper Hastrup; Olesen, Søren-Peter; Sørensen, Ulrik S.; Jespersen, Thomas; et al.
Abstract : Background: Evidence has emerged that small-conductance Ca 2+ -activated K + (SK) channels constitute a new target for treatment of atrial fibrillation (AF). SK channels are predominantly expressed in the atria as compared with the ventricles. Various marketed antiarrhythmic drugs are limited by ventricular adverse effects and efficacy loss as AF progresses. Methods and Results: A total of 43 pigs were used for the studies. AF reversion in conscious long-term tachypaced pigs: Pigs were subjected to atrial tachypacing (7 Hz) until they developed sustained AF that could not be reverted by vernakalant 4 mg/kg (18.8±3.3 days of atrial tachypacing). When the SK channel inhibitor AP14145 was tested in these animals, vernakalant-resistant AF was reverted to sinus rhythm, and reinduction of AF by burst pacing (50 Hz) was prevented in 8 of 8 pigs. Effects on refractory period and AF duration in open chest pigs: The effects of AP14145 and vernakalant on the effective refractory periods and acute burst pacing-induced AF were examined in anaesthetized open chest pigs. Both vernakalant and AP14145 significantly prolonged atrial refractoriness and reduced AF duration without affecting the ventricular refractoriness or blood pressure in pigs subjected to 7 days atrial tachypacing, as well as in sham-operated control pigs. Conclusions: SK currents play a role in porcine atrial repolarization, and pharmacological inhibition of these with AP14145 demonstrates antiarrhythmic effects in a vernakalant-resistant porcine model of AF. These results suggest SK channel blockers as potentially interesting anti-AF drugs. Abstract : Supplemental Digital Content is available in the text.